A facile approach to superhydrophilic-superhydrophobic patterns in porous polymer films - Zahner, David; Abagat, Joselle; Svec, Frank; Fréchet, Jean M. J.; Levkin, Pavel (Advanced materials, 2011)
A facile and versatile method for creating superhydrophilic patterns in superhydrophobic porous polymer films by UV-initiated photografting is presented. The extreme difference in wettability between superhydrophilic and superhydrophobic areas allows the use of the superhydrophilic patterns as virtual microfluidic channels. The method allows for precise control of the size and geometry of photografted superhydrophilic features, and the thickness, morphology, and transparency of the superhydrophobic and hydrophobic porous polymer films.
Gesehen am 19.12.2022